Consumo de forragem por novilhas de corte em pastagem de azevém e recebendo farelo de arroz com e sem ionóforo - Eloy, Lidiane Raquel (2013)
The forage intake was evaluated in beef heifers at grazing exclusive ryegrass (Lolium multiflorum Lam.) or receiving rice bran, with and without ionophore. We used the method of continuous grazing with variable number of animals. Rice bran in the proportion of 0.80% of body weight, was administered daily at 14 hours and showed levels of 13.80% crude protein (CP), 25.79% of neutral detergent fiber (NDF) and 12.45% ether extract (EE). The experimental design was completely randomized with repeated measures over time.Was used chromic oxide as a fecal production indicator. The dry matter intake was estimated using the technique of chromium oxide as an indicator of fecal output. The beef heifers grazing exclusively on pasture intake had a similar those receiving rice bran with or without monensin (2.63% of the BW in DM). The highest total dry matter intake was observed in heifers remained in ryegrass and received rice bran with addition of ionophore (3.42% of the BW in DM), intermediate in heifers that received rice bran (3.26% of the BW in DM) and remained lower in heifers grazing ryegrass (2.82% of the BW in DM). Average daily gain was higher for beef heifers receiving ionophore added to rice bran. The stocking rate was similar between food systems tested.